1990
DOI: 10.1002/ijc.2910450313
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of P53 protein and dna content of colorectal adenocarcinomas by flow cytometry

Abstract: The p53 transformation-related gene is located on 17p, a chromosomal segment frequently under-represented in colorectal adenocarcinoma karyotypes. We have developed a flow cytometric method for detection of its gene product on isolated nuclei by indirect immunofluorescence. Criteria for defining the presence of p53 were established, using parameters related to the difference of fluorescence obtained by incubating nuclei with a specific monoclonal antibody (MAB) versus isotypic control. This method allowed simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 22 publications
2
38
0
2
Order By: Relevance
“…Baker et al (1989) has demonstrated mutation of the p53 gene in two tumours associated with increased mRNA production. Remvikos et al (1990) found a significant association between elevated p53 and the presence of DNA aneuploidy but not Dukes' stage. They did not however investigate cell proliferation or prognosis.…”
Section: Discussionmentioning
confidence: 80%
“…Baker et al (1989) has demonstrated mutation of the p53 gene in two tumours associated with increased mRNA production. Remvikos et al (1990) found a significant association between elevated p53 and the presence of DNA aneuploidy but not Dukes' stage. They did not however investigate cell proliferation or prognosis.…”
Section: Discussionmentioning
confidence: 80%
“…Statistical analysis of follow-up data of 47 patients with gastric carcinoma (20 with p53 positive and 27 with p53 negative tumours) and of 80 patients operated on for colorectal cancer (36 with p53 positive and 44 with p53 negative tumours), revealed that p53 overexpression in both carcinomas is significantly associated with early relapse and death (P<0.001). Thus,18 (Crawford et al, 1984;Remvikos et al, 1990;Rodrigues et al, 1990;Scott et al, 1991;Campo et al, 1991 (Fielding & Priestman, 1986;Preece et al, 1986). The prognosis is worse for cancers which originate in the upper third of stomach or in the rectum.…”
Section: Resultsmentioning
confidence: 99%
“…It also has been demonstrated that colorectal carcinomas of the fungating type metastasised less frequently than ulcerative tumours (Fielding & Priestman, 1986 There is no published data on the prognostic significance of p53 protein in gastric cancer and little is known about its role in determining prognosis in colorectal carcinoma. Remvikos et al (1990), investigated 41 colorectal tumours and found a significant association between elevated p53 and the presence of DNA aneuploidy, a factor connected with poor prognosis but not with Dukes stage. They suggested that evaluating p53 expression may prove useful in determining different biological subgroups of colorectal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in this gene constitute some of the most frequently occurring genetic changes at human malignancies and are thought to be late development in the adenoma -carcinoma sequence in CRC (Fearon and Vogelstein, 1990). Mutations in this gene increase the protein half-life and are often associated with protein overexpression in the nucleus (Remvikos et al, 1990). Mutations most commonly occur in the highly conserved region (exons 5 -8), which encodes the DNAbinding domain (Zhang et al, 1997).…”
mentioning
confidence: 99%